The endoplasmic reticulum as a calcium gateway in programmed cell death - Demaurex, Nicolas (Henry Stewart Talks, 2007)
Calcium signals: cardiac contraction, Intracellular calcium signals, The calcium language of cells, Cellular sources of calcium, "Calciosomes": the ER and mitochondria, Calcium probes, ER and mitochondria dynamics, ER calcium signals, Mitochondrial calcium signals, Mitochondrial calcium paradox, The ERmitochondria connection, Calcium and mitochondrial permeability, ER calcium load, Bcl-2 family proteins, Protective effect of ER depletion, Bax/Bak ablation, Apoptosis: the calcium connection
Archived at 2020/08/13